Drainage pattern and flow estimation at section 1, Bandar Baru Bangi - Muhammad Amirul, Mohd Zaini (2018)
Drainage system is important systems which function to control surface runoff and decreasing the bad effect to earth surface. Proper drainage system is important to manage surface runoff while improper drainage system will causes some problem to environment such as flooding, erosion, odor and health hazard. Study area in this project is at Section 1, Bandar Baru Bangi. The objectives of this study case are to determine the drainage pattern, to estimate the maximum flow of the drainage system and to check the drainage capacity of 2 years ARI, 5 years ARI and 10 years ARI in the study area. The methods involved are the Average Rainfall Station, Rational Method and the Manning’s Formula. The Average Rainfall Method is used to identify the missing value in the rainfall data provided by Department of Irrigation and Drainage Malaysia. The Rational Method is used to calculate the peak discharge while the Manning’s Formula is used to determine the capacity of drainage. The result of this study is to justify whether the existing drain are still able to support the amount of rainfall intensity the design of the drainage can support the intensity of the rainfall.